Prostate brachytherapy in Ghana: our initial experience - Mensah, James Edward; Yarney, Joel; Vanderpuye, Verna; Akpakli, Evans; Tagoe, Samuel; Sasu, Evans (Journal of Contemporary Brachytherapy, 2016)
Purpose: This study presents the experience of a brachytherapy team in Ghana with a focus on technology transfer and outcome. The team was initially proctored by experienced physicians from Europe and South Africa. Material and methods : A total of 90 consecutive patients underwent either brachytherapy alone or brachytherapy in combination with external beam radiotherapy for prostate carcinoma between July 2008 and February 2014 at Korle Bu Teaching Hospital, Accra, Ghana. Patients were classified as low-risk, intermediate, and high-risk according to the National Comprehensive Cancer Network (NCCN) criteria. All low-risk and some intermediate risk group patients were treated with seed implantation alone. Some intermediate and all high-risk group patients received brachytherapy combined with external beam radiotherapy. Results: The median patient age was 64.0 years (range 46-78 years). The median follow-up was 58 months (range 18-74 months). Twelve patients experienced biochemical failure including one patient who had evidence of metastatic disease and died of prostate cancer. Freedom from biochemical failure rates for low, intermediate, and high-risk cases were 95.4%, 90.9%, and 70.8%, respectively. Clinical parameters predictive of biochemical outcome included: clinical stage, Gleason score, and risk group. Pre-treatment prostate specific antigen (PSA) was not a statistically significant predictor of biochemical failure. Sixty-nine patients (76.6%) experienced grade 1 urinary symptoms in the form of frequency, urgency, and poor stream. These symptoms were mostly self-limiting. Four patients needed catheterization for urinary retention (grade 2). One patient developed a recto urethral fistula (grade 3) following banding for hemorrhoids. Conclusions : Our results compare favorably with those reported by other institutions with more extensive experience. We believe therefore that, interstitial permanent brachytherapy can be safely and effectively performed in a resource challenged environment if adequate training and proctoring is provided.